Legal Regime of AI-Generated Outputs - M. V. Samartseva (Цифровое право, 2025)
The article is devoted to the study of the legal nature of generative artificial intelligence and its impact on copyright. It examines the features of generative artificial intelligence, which is capable of creating new content in response to user requests (prompts). The focus is on the legal evaluation of results generated using artificial intelligence technologies (the AI outputs) and their comparison with the results of intellectual activity created by humans. The article analyzes the criteria for the protectability of such AI results in the context of Russian legislation and existing international approaches. The author emphasizes that the results of AI created without human participation, within the meaning of the law, cannot be recognized as objects of copyright under Russian Federation law due to the lack of creative contribution and direct human involvement in their creation. Instead, it is proposed to develop a special legal regime for such objects—AI results—that will ensure their economic value and legal protection. Possible legal mechanisms are also considered as tools to protect the results created using AI, provided that there is a significant human creative contribution. The article emphasizes the need for a clear distinction between objects created by AI autonomously, without human participation, and objects created as a result of human creative activity using AI as a creative tool. The author offers regulatory provisions for the regulation of property rights to results generated by AI and considers the prospects for the development of legislation in this area.